PENGARUH HARGA, KUALITAS PRODUK DAN LOKASI TERHADAP KEPUTUSAN PEMBELIAN PRODUK KAIN SASAMBO DI MUTMAINAH KOTA BIMA - Ovriyadin Ovriyadin; Hardian Reza Dharmansyah; Indra Darmawansyah (CAPITAL: Jurnal Ekonomi dan Manajemen, 2023)
: When consumers buy the same product at a higher price and then find the same product at a lower price, it will certainly affect their purchasing decision. Apart from the price factor, the product quality factor as seen from the attractive product design will influence consumer purchasing decisions. If the quality of a product meets the needs and desires of consumers, then consumers will not care about the price given or feel they will not regret the quality that has been given to buy the product and consumers who buy it for the first time find it difficult to reach locations because of the route. in the same direction. The purpose of this study was to analyze the effect of price, product quality, location on purchasing decisions, both partially and simultaneously. The population is all consumers of mutmainah shops who have bought sasambo cloth, while the sampling technique in this study was using an accidental sampling technique, and using 96 respondents. The analysis technique used is multiple linear regression, correlation coefficient, determination test, t test and F test. The results show that: 1) Price, quality partially affect the purchasing decision at the mutmainah kota bima store, while the location has no effect on the purchasing decision. 2) Simultaneously price, quality and location affect consumer decisions at the mutmainah kota bima store